Palm Springs weekend [videorecording (DVD)] - Taurog, Norman, 1899-1981; Donahue, Troy, 1936-2001; Stevens, Connie, 1938-; Hardin, Ty, 1930-2017; Powers, Stefanie; Conrad, Robert, 1935-2020-; Weston, Jack, 1924-1996 (Warner Home Video, 2009)
It's Spring Break 1963, and everyone is headed for the California desert playground of Palm Springs.